Postpartum bonding: the impact of maternal depression and adult attachment style - Nonnenmacher, Nora; Noe, Daniela; Ehrenthal, Johannes C. (Archives of women's mental health, 2016)
Maternal depression poses a risk for the developing mother-infant relationship. Similarly, maternal insecure attachment styles may limit the ability to adequately connect with the newborn during the postpartum period. The aim of this study was to investigate the effect of maternal depression and insecure attachment (insecure and dual/disorganized) on maternal bonding in a sample of n = 34 women with depression according to DSM-IV and n = 59 healthy women. Maternal depression was assessed 3 to 4 months postpartum with the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-I), bonding with the Postpartum Bonding Questionnaire, and maternal attachment style with the Attachment Style Interview. Women with current and lifetime depression as well as women with dual/disorganized attachment style reported lower bonding. Explorative analysis revealed that depression partially mediated the link between dual/disorganized attachment style and bonding with a medium-sized mediation effect. The combination of maternal depression and dual/disorganized attachment style may pose a special risk constellation for the developing mother-infant bond that should be addressed in prevention and early intervention programs.